Proposal to optimize the admission of workers through the basic principles of information management (Research, Society and Development, 2021)
This article discusses a topic that, according to the representative of the company UPTEC Construção e Tecnologia Ltda.  (UPTEC) have been a bottleneck between the production sector and the admission: the release of the worker, even after he hasbeen approved to be admitted to the company. The problem is that some workers tend not to present two types of certificates of mandatory possession in electrical areas, according to the Regulatory Standard (NR), NR-10, item 10.8/Training, posted in  Ministerial Ordinance No. 3.214/Safety and Medicine of the Work (SMT) (BRASIL, 1978): one is related to a basic course, where the basic rules about work in electricity are given, such as rights and duties in areas of prevention and the other course is about the Electric Power System (SEP), where topics related to the profession, such as how to work safely with a view to productivity. In order to carry out this study, data and information were collected via e-mail for some workers in the electrical sector, with a view to knowing how they were presenting / delivering the certificates required in item 10.8 / NR-10. To process the data, the Windows® operating system was used, on the Excel platform, to tabulate and some quality tools, such as the check sheet, the histogram, the Pareto graph. The results of the study pointed out that the use of quality tools can assist in making managerial decisions and as a proposal to improve the admission process, an action plan was developed.